Ranolazine in patients with incomplete revascularisation after percutaneous coronary intervention (RIVER-PCI): a multicentre, randomised, double-blind, placebo-controlled trial - Weisz, Giora; Généreux, Philippe; Iñiguez, Andres; Zurakowski, Aleksander; Shechter, Michael; Alexander, Karen P; Dressler, Ovidiu; Osmukhina, Anna; James, Stefan; Ohman, E Magnus; Ben-Yehuda, Ori; Farzaneh-Far, Ramin; et al. (The Lancet (British edition), 2016)
Incomplete revascularisation is common after percutaneous coronary intervention and is associated with increased mortality and adverse cardiovascular events. We aimed to assess whether adjunctive anti-ischaemic pharmacotherapy with ranolazine would improve the prognosis of patients with incomplete revascularisation after percutaneous coronary intervention. We performed this multicentre, randomised, parallel-group, double-blind, placebo-controlled, event-driven trial at 245 centres in 15 countries in Europe, Israel, Russia, and the USA. Patients (aged ≥18 years) with a history of chronic angina with incomplete revascularisation after percutaneous coronary intervention (defined as one or more lesions with ≥50% diameter stenosis in a coronary artery ≥2 mm diameter) were randomly assigned (1:1), via an interactive web-based block randomisation system (block sizes of ten), to receive either twice-daily oral ranolazine 1000 mg or matching placebo. Randomisation was stratified by diabetes history (presence vs absence) and acute coronary syndrome presentation (acute coronary syndrome vs non-acute coronary syndrome). Study investigators, including all research teams, and patients were masked to treatment allocation. The primary endpoint was time to first occurrence of ischaemia-driven revascularisation or ischaemia-driven hospitalisation without revascularisation. Analysis was by intention to treat. This study is registered at ClinicalTrials.gov, number NCT01442038. Between Nov 3, 2011, and May 27, 2013, we randomly assigned 2651 patients to receive ranolazine (n=1332) or placebo (n=1319); 2604 (98%) patients comprised the full analysis set. After a median follow-up of 643 days (IQR 575–758), the composite primary endpoint occurred in 345 (26%) patients assigned to ranolazine and 364 (28%) patients assigned to placebo (hazard ratio 0·95, 95% CI 0·82–1·10; p=0·48). Incidence of ischaemia-driven revascularisation and ischaemia-driven hospitalisation did not differ significantly between groups. 189 (14%) patients in the ranolazine group and 137 (11%) patients in the placebo group discontinued study drug because of an adverse event (p=0·04). Ranolazine did not reduce the composite rate of ischaemia-driven revascularisation or hospitalisation without revascularisation in patients with a history of chronic angina who had incomplete revascularisation after percutaneous coronary intervention. Further studies are warranted to establish whether other treatment could be effective in improving the prognosis of high-risk patients in this population. Gilead Sciences, Menarini.